THE ROLE OF SOCIAL MEDIA ON MIGRATION DECISION-MAKING PROCESSES: Case of Indonesian Student in University of Groningen - Inayah Hidayati (Jurnal Studi Pemuda, 2017)
Objective: This research aims to explain the impact of social media on the migration decision-making process of Indonesian student migrants in University of Groningen who used a social media account. In detail, this research will consider the role of social media in the migration decision-making process of students who emigrated from Indonesia and how they uses social media in the context of the migration decision-making process. Methods: The data collected included qualitative data from in-depth interviews and supported by study literatures. An interview guide was formulated to facilitate the indepth interviews and generate a better understanding of migration behavior. Expectation: Social media help Indonesian student migrants on migration decision making process and they use social media for searching information about destination area. Result: Student migrant in University of Groningen use their social media to gain information before they choose that university for study. They use Facebook to making contact with their friends and collagues in the destination country. Student group on Facebook help Indonesian student to get information about school and daily life.